1954
DOI: 10.1001/jama.1954.02950100023009
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Systemic Lupus Erythematosus

Abstract: In our case the participation of lipid deposits in the structural abnormalities of calcific aortic stenosis cannot be questioned. Nests of lipophages or foam cells and deposits of cholesterol crystals are apparent on the sur¬ face of the valve, in its substance, at its base, and in the endocardium proximal to it. These characteristic stigmas of atherosclerosis or xanthomatosis are surrounded by partially calcified fibrous tissue. The lesions in the valve resemble closely the classical atherosclerotic changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1955
1955
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Ropes and other early investigators also reported that spontaneous remissions lasting a few months to several years occurred in 35-70% of untreated patients (16)(17)(18). More recent studies differ in reported remission rates, partly because of differences in the duration of followup and the definition of remission used, including the need to not be taking any medications, the absence of serologic activity, and the minimum duration of disease quiescence.…”
Section: Discussionmentioning
confidence: 98%
“…Ropes and other early investigators also reported that spontaneous remissions lasting a few months to several years occurred in 35-70% of untreated patients (16)(17)(18). More recent studies differ in reported remission rates, partly because of differences in the duration of followup and the definition of remission used, including the need to not be taking any medications, the absence of serologic activity, and the minimum duration of disease quiescence.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4] Standard textbooks of pulmonary medicine relate the progressive dyspnea, small lung volume with elevated hemi diaphragms to ''an unspecified restriction in chest wall expansion'' generally ascribed to diaphragmatic weakness. 5 Investigators have hypothesized or measured defects in lung recoil, 1 phrenic nerve function 6 and diaphragmatic strength.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence was obtained that a decrease in serum heat-labile opsonin concentration was in fact responsible for the defect. It was also shown that the defect in phagocytosis was not due to the presence of leukocytotoxic antibodies (6,7) in the deficient SLE sera by the successful restoration of opsonic capacity upon addition of normal serum in 12 of 16 experiments. The less than complete restoration observed with occasional sera of this group may have been due to consumption of critical complement components of the added normal serum during the 1 and 2-h phagocytosis periods by the active SLE sera present, since the latter are known to contain immune complexes and to be anti-complementary (31).…”
Section: Methodsmentioning
confidence: 98%
“…The increased susceptibility of patients with active systemic lupus erythematosus (SLE)1 to bacterial and mycotic infections has been well documented (1)(2)(3)(4)(5)(6)(7)(8). Al-though the introduction of corticosteroid therapy may currently be a contributing factor, infections constituted a frequent cause of death in the precorticosteroid era (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%